Fetal Hydantoin Syndrome and Its Anaesthetic Implications: A Case Report - Ranju Singh; Nishant Kumar; Sakshi Arora; Ritu Bhandari; Aruna Jain (Case Reports in Anesthesiology)
Fetal hydantoin syndrome is a rare disorder that is believed to be caused by exposure of a fetus to the anticonvulsant drug phenytoin. The classic features of fetal hydantoin syndrome include craniofacial anomalies, prenatal and postnatal growth deficiencies, underdeveloped nails of the fingers and toes, and mental retardation. Less frequently observed anomalies include cleft lip and palate, microcephaly, ocular defects, cardiovascular anomalies, hypospadias, umbilical and inguinal hernias, and significant developmental delays. Anaesthesia for incidental surgery in such a patient poses unique challenges for the anesthesiologist. We report the successful management of a 4-year-old male child with fetal hydantoin syndrome, cleft palate, spina bifida, atrial septal defect, and dextrocardia for tibialis anterior lengthening under subarachnoid block.